ANALYSIS OF SPHERICAL ASTRONOMY ALGORITHMS FOR PREDICTING THE SOLAR ECLIPSE BY W.M. SMART - Fiki Nuafi Qurrota Aini; Ahmad Luqman Hakim (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
A solar eclipse is an unusual natural occurrence. Muslims used the phenomenon of a solar eclipse as the season for prayer, which was only carried out during a solar eclipse from early in the phenomenon until the end. Although there is no statistically significant difference in estimating a solar eclipse, as the seasons change, a solar eclipse becomes increasingly important. Lots of alternatives can be used as a reference in the determination of a solar eclipse. Among the alternatives commonly used is the calculation of spherical astronomy. Despite its complexity, many people still use it as the foundation for calculations based on solar eclipse Pythagoras as well as the determination of the celestial coordinate system.